Homozygous p.Val89Leu plays an important pathogenic role in 5α-reductase type 2 deficiency patients with homozygous p.Arg246Gln in SRD5A2. Issue 3 (September 2020) - Arya, Sneha; Tiwari, Ankita; Lila, Anurag Ranjan; Sarathi, Vijaya; Bhandare, Vishwambhar Vishnu; Kumbhar, Bajarang Vasant; Rai, Khushnandan; Kunwar, Ambarish; Thakkar, Hemangini; Thakkar, Kunal; Memon, Saba Samad; Patil, Virendra; et al.
Abstract : Objective: : To evaluate the pathogenic role of a few benign variants and hypomorphic pathogenic variants in SRD5A2 . Design and methods: : We retrospectively analyzed phenotypes and genotypes in 23 Indian patients with genetically proven steroid 5α-reductase 2 (SRD5A2) deficiency. The interactions of the SRD5A2 enzymes resulting due to the most common benign variant (p.Val89Leu), the most common (hypomorphic) pathogenic variant (p.Arg246Gln) and the double variants (p.Val89Leu and p.Arg246Gln) in SRD5A2 were compared with that of the wild type (WT) enzyme by molecular dynamics (MD) simulation. Results: : The majority ( n  = 19, 82.61%) of patients presented for atypical genitalia and had male gender identity (16/20). Including the two novel ones (p.Leu83Pro, p.Ala28Leufs*103), a total of nine different pathogenic variants were observed. p.Arg246Gln was the most common pathogenic variant ( n  = 12). Homozygous p.Arg246Gln ( n  = 9) variant was associated with milder undervirilization (Sinnecker score of ≤3a: 8/9 vs 6/14, P  = 0.04) and had concurrent homozygous p.Val89Leu in all patients. Interestingly, asymptomatic fathers of two index patients were homozygous for p.Arg246Gln which questioned the pathogenicity of the variation as a sole factor. Unlike all symptomatic homozygous p.Arg246Gln patients who were also homozygous for p.Val89Leu, asymptomatic homozygous p.Arg246Gln fathers were heterozygous for p.Val89Leu. On MD simulation SRD5A2 p.Val89Leu-Testeosterone (T) and SRD5A2 p.Arg246Gln-T complexes, but not SRD5A2 p.Val89Leu and p.Arg246Gln-T complex, demonstrated close interaction between NADPH and T as that of SRD5A2 WT-T. Conclusions: : p.Arg246Gln may not be pathogenic as a sole variation even in the homozygous state; additional contribution of homozygous p.Val89Leu variant may be essential for the pathogenicity of p.Arg246Gln in SRD5A2 .